Doping Platinum with Germanium: An Effective Way to Mitigate the CO Poisoning. Issue 15 (17th June 2021) - Ugartemendia, Andoni; Peeters, Kristien; Ferrari, Piero; de Cózar, Abel; Mercero, Jose M.; Janssens, Ewald; Jimenez‐Izal, Elisa
Abstract: The vulnerability towards CO poisoning is a major drawback affecting the efficiency and long‐term performance of platinum catalysts in fuel cells. In the present work, by a combination of density functional theory calculations and mass spectrometry experiments, we test and explain the promotional effect of Ge on Pt catalysts with higher resistance to deactivation via CO poisoning. A thorough exploration of the configurational space of gas‐phase Pt n + and GePt n −1 + ( n =5–9) clusters using global minima search techniques and the subsequent electronic structure analysis reveals that germanium doping reduces the binding strength between Pt and CO by hindering the 2π‐back‐donation. Importantly, the clusters remain catalytically active towards H2 dissociation. The ability of Ge to weaken the Pt−CO interaction was confirmed by mass spectrometry experiments. Ge can be a promising alloying agent to tune the selectivity and improve the durability of Pt particles, thus opening the way to novel catalytic alternatives for fuel cells. Abstract : CO poisoning of Pt catalysts is one of the major obstacles for the commercialization of Fuel Cells. Here by a combination of DFT calculations and mass spectrometric experiments, it is demonstrated that Ge doping mitigates the CO poisoning propensity of Pt nanoclusters, while they remain catalytically active for H2 dissociation.